1998
DOI: 10.1016/s0014-5793(98)00980-6
|View full text |Cite
|
Sign up to set email alerts
|

Photovoltage evidence that Glu‐204 is the intermediate proton donor rather than the terminal proton release group in bacteriorhodopsin

Abstract: Electrogenic events in the E204Q bacteriorhodopsin mutant have been studied. A two-fold decrease in the magnitude of microsecond photovoltage generation coupled to M intermediate formation in the E204Q mutant is shown. This means that deprotonation of E204 is an electrogenic process and its electrogenicity is comparable to that of the proton transfer from the Schiff base to D85. pH dependence of the electrogenicity of M intermediate formation in the wild-type bacteriorhodopsin reveals only one component corres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…One of the first questions that needed to be addressed for understanding the second proton transfer step (from the extracellular proton release group to the extracellular bulk) was the exact nature of the proton release group. Earlier experiments indicated the involvement of E204 either as the proton release group [80] or as the group that delivers the released proton to E194 [81,82]. Based on more recent data, it was proposed that the proton is stored in a cluster of water molecules that interacts with protein amino acids [83,84].…”
Section: Long-distance Proton Transfersmentioning
confidence: 99%
“…One of the first questions that needed to be addressed for understanding the second proton transfer step (from the extracellular proton release group to the extracellular bulk) was the exact nature of the proton release group. Earlier experiments indicated the involvement of E204 either as the proton release group [80] or as the group that delivers the released proton to E194 [81,82]. Based on more recent data, it was proposed that the proton is stored in a cluster of water molecules that interacts with protein amino acids [83,84].…”
Section: Long-distance Proton Transfersmentioning
confidence: 99%
“…A number of studies performed on mutated BR suggest that Glu‐194 and Glu‐204, within a hydrogen‐bonded network, form part of the proton release pathway [15–23]. However, the source of the released proton in the extracellular space, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it can be concluded that E194 and E204 play a crucial role in proton release and E9 as well as E74 are not necessary for normal proton transfer to the extracellular membrane surface. Recently, several authors suggested that the released proton originates from E204 (or several groups including E204: the E204 site), whereas E194 acts as the acceptor of the proton from the E204 site and as the proton donor to the membrane surface (27,29,30). Because a band due to deprotonation of E204 (28, 31) or E194 (28) is not observed in time-resolved infrared difference spectra it was concluded that the proton is released by a hydrogen-bonded network connecting D85 and E204 and possibly including E194 and bound water.…”
mentioning
confidence: 99%